La reconnaissance du corps vivant et du corps d’autrui - Failla, Mariannina (B@belonline, 2024)
The issue will discuss the theme of acknowledgement on the basis of the Husserlian Leiblichkeit, this analysis draws on the category of relationality, both intra-bodily (‘to acknowledge one’s own psycho-corporal unity’) and inter-bodily (to acknowledge the ‘other’). The paper then focuses on the centrality of the environment, representing the milieu in which the experience of acknowledgement between bodies takes place. Acknowledgement involves two moments: the experience of disposing of one’s acts and psycho-corporal states (time and its phenomenological constitution), and the experience of the relationship between two bodies, through the coordinates of spatial orientation in the environment (the movement of living or experienced bodies in space). The word ‘environment’ thus becomes synonymous with spatio-temporal relations which, as we shall see, form the basis of a twofold process of acknowledgement.